(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Parents child relationship is one of the most important unique relationship which carries special blend of nurture like physical, emotional and social progression in a child. In this relationship the development of personality, behaviour and life of an individual may takes shape and individuals ability to adjust and regulate his or her behaviour deep rooted in parent’s child relationship. But as child steps ahead in adolescence he or she start experiencing many changes from all aspects of life and sometimes these changes brings many challenges for adolescence. And one of the most major challenge that a teenager faced adjustment in parent child relationship. To take into account, this study is assessed the adolescents problems and its impact on parents child relationship. Aims and Objectives- to examine the parent’s child relationship and youth problem in different areas of life in teenagers. Material and Methods- to fulfil this purpose a purposive sample of 100 teenagers (age between 12 to 18 years) was administered by using the Parent Child Relationship Scale and Youth Problem Inventory as tools. Results – there is no significant difference on relationship with mother and father on the basis of gender as well there is also no significant difference on youth problems in gender but both male and females are facing problem in family, academics and in personal issues etc . Conclusion- for the betterment and healthy life and the overall development of personality as an adult it is very important to proposed researches on relationship of parent and child and different youth problems.